WEB-APPLICATION DESIGN FOR LOW-COST AIR QUALITY MONITORING SYSTEM - Joel Hermesha, Wiennetou
Clean air is a vital necessity for all living things, including people. However, due to exceeding WHO quality guidelines for PM2.5 (particles smaller than 2.5 microns above 15 ug/m3), PM10 (particles smaller than 10 microns above 15 ug/m3), as well as carbon monoxide, the air pollution level in the city of Bandung is quite high. Dinas Lingkungan Hidup dan Kebersihan (DLHK) Kota Bandung only has 1 monitoring device with a radius of measuring range of only 500 m, making it impossible to properly monitor these significant air pollutants. Due to this, monitoring of the air quality is only done for 0.469% of Bandung City's entire area. The government is unable to increase the number of air quality monitoring units because the equipment costs DLHK 400 million rupiah and requires expensive routine maintenance. This means that the tool's pollutant statistics cannot accurately represent the city of Bandung's total air quality. Additionally, it still requires manual work to transfer and process data from the air quality monitoring equipment to DLHK in Bandung City, and it takes two weeks to collect the data and one month to process it in the lab. Not only that, but existing pollutant data cannot be sent at any time to the government's air quality monitoring application (ISPUnet), preventing the public from knowing the most recent air quality data and making it challenging for DLHK to respond to complaints or other public complaints when they arise. This study suggests a low-cost online application for monitoring air quality that is connected to the cloud and created with React Javascript to address this issue. This web application can be accessed by users on desktop computers or mobile devices. To display real-time data on the Indeks Standar Pencemar Udara (ISPU), Particular Matter (PM), CO, temperature, and humidity, the web application once every minute requests API data from PostgreSQL. Users of this web application can review historical data in hourly, daily, or weekly timelines using the graphs provided. Additionally, users can view in real-time the five sites with the highest ISPU scores as well as WHO recommendations for each location's air quality. The administrator of this web application, DLHK Kota Bandung, also has the ability to update the registered device location database and can see which locations are actively sending air quality data.